PHYSICO-CHEMICAL ASSESSMENT OF SOILS USED FOR VEGETABLE CULTIVATION IN KURA REGION OF KANO STATE, NIGERIA - Yakasai, Umma Abdurrahman; Rabiu, Safianu (FUDMA Journal of Sciences, 2024)
The research was conducted with the aim of assessing the physico-chemical parameters of soils used for vegetable cultivation in Kura region of Kano State, Nigeria. Soil samples were collected from three onion plots, three tomato plots and three cucumber plots from the top (0-20cm) in the sites. Standard laboratory procedures were used to assess the samples for PH, organic matter, nitrogen, available phosphorous, and potassium contents. In addition, the mean values of soil parameters determined were computed and the results was compared with the critical limits in other to interpret level of the soils fertility. The results of the assessment revealed that the soil samples had low to moderate PH (5.28-6.71), and organic matter concentrations (0.44-1.86%), low potassium concentrations (0.05-0.21mol/kg), moderate to high nitrogen (0.14-0.44%) and high phosphorous concentrations (22.07-55.49mg/kg). Since nitrogen can be recycled in nature, efforts should be made to recycle the excess phosphorous in soils of vegetable crops plots. Furthermore, it is recommended to promote the use of bio-fertilizers such arbuscular mycorrhizal fungi (AMF) inoculants, which may dissolve and transfer essential nutrients from the soil to the plants.